Selection of the Winding Type of Solid-State Transformers in Terms of Transmitting the Greatest Possible Power in the Frequency Range from 500 Hz to 6000 Hz - Elzbieta Lesniewska; Daniel Roger (Energies, 2023)
Solid-state transformer (SST) is an emerging technology that integrates with transformer power electronics converters and control. The most noticeable advantages of SST are the size and weight reduction compared with low-frequency transformers. Since this device is used in many devices such as smart grids, traction systems, systems with renewable energy sources (RESs) and electric vehicle charging devices, it is important to build a high-efficiency device at a low cost. The article evaluates a medium frequency transformer (SST) operating at a frequency of 500 Hz to 6000 Hz with coils wound with aluminum foil or Litz windings and of a grain-oriented electrical steel (GOES) core. The calculations were made using the 3D field method using the numerical finite element method, and the results were compared with the tests of the real model. The measurement method based on the Fourier analysis of real signals was used for the research.